Penerapan Model Pembelajaran Jigsaw untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV Sekolah Dasar - Tombokan, Sarah S.N (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to apply the jigsaw learning model to improve social studies learning outcomes for class IV students at Don Bosco Bitung 2 Catholic Elementary School. The method used is Classroom Action Research by Kemmis and MC. Tanggart includes four stages, namely: (1) Planning, (2) Action, (3) Observation, (4) Reflection which is carried out in two cycles. The subjects of this research were class IV students using the jigsaw learning model. Data collection techniques are carried out through observation and evaluation of students who are studying using observation sheets and written tests are carried out to measure students' understanding abilities regarding the lessons given. The data analysis technique uses the KB formula = T/Tt x 100%. The research results show cycle I = 63% and cycle II = 86.33%. From the research results, it can be concluded that the application of the Jigsaw learning model can improve social studies learning outcomes and help students work more actively in groups, especially fourth grade students at Don Bosco Bitung 2 Catholic Elementary Schoo